Glycosyltransferases: structures and mechanisms - Palcic, Monica (Henry Stewart Talks, 2012)
Reactions catalyzed by glycosyltransferases: substrates and products, Glycosyltransferase structural folds, History of Blood group A and B enzymes as models for glycosyltransferase structures and mechanisms, Properties of natural and unnatural blood group A and B glycosyltransferase mutants
Archived at 2022/07/05